Activating Phosphoenolpyruvate Carboxylase and Phosphoenolpyruvate Carboxykinase in Combination for Improvement of Succinate Production - Tan, Zaigao (American Society for Microbiology, 2013)
Phosphoenolpyruvate (PEP) carboxylation is an important step in the production of succinate by Escherichia coli. Two enzymes, PEP carboxylase (PPC) and PEP carboxykinase (PCK), are responsible for PEP carboxylation. PPC has high substrate affinity and catalytic velocity but wastes the high energy of PEP. PCK has low substrate affinity and catalytic velocity but can conserve the high energy of PEP for ATP formation. In this work, the expression of both the ppc and pck genes was modulated, with multiple regulatory parts of different strengths, in order to investigate the relationship between PPC or PCK activity and succinate production. There was a positive correlation between PCK activity and succinate production. In contrast, there was a positive correlation between PPC activity and succinate production only when PPC activity was within a certain range; excessive PPC activity decreased the rates of both cell growth and succinate formation. These two enzymes were also activated in combination in order to recruit the advantages of each for the improvement of succinate production. It was demonstrated that PPC and PCK had a synergistic effect in improving succinate production.